Re-lift enhanced positive output superlift luo converter - Lim, Hong Wei (2016)
This project aims to design and build controllers to regulate the output voltage of the Re-lift enhanced positive super lift Luo converter and Cuk converter. In this report, it will discuss and present the theoretical knowledge, circuitry designs, implementation and control of the re-lift enhanced Luo converter. A hysteresis sliding mode current controller was used to control the output voltage of the converter. The controller was designed to track the voltage change and interference load test requirements to determine the robustness. Experimental results will be presented to verify that these requirements were achieved. At the same time, it will also present the simulation of the Cuk converter with adaptive current mode controller.